2021
DOI: 10.3390/ijms22168785
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and Teratogenic Effects of Prenatal Alcohol Exposure on Fetal Development, Adolescence, and Adulthood

Abstract: Prenatal alcohol exposure (PAE) can have immediate and long-lasting toxic and teratogenic effects on an individual’s development and health. As a toxicant, alcohol can lead to a variety of physical and neurological anomalies in the fetus that can lead to behavioral and other impairments which may last a lifetime. Recent studies have focused on identifying mechanisms that mediate the immediate teratogenic effects of alcohol on fetal development and mechanisms that facilitate the persistent toxic effects of alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 202 publications
0
13
0
Order By: Relevance
“…Many studies have suggested that epigenetic modification is involved in the abnormal development of multiple organs in offspring exposed to adverse environments during pregnancy. [61][62][63] For example, prenatal dexamethasone exposure could inhibit the H3K27ac level and expression of adrenal IGF1 via the GRα/miR-370-3p/Sirt3 pathway, and programmed the adrenal hypofunction of offspring. 64 In this study, we found that the level of H3K14ac in the promoter region of SR-B1 of the PCE female offspring increased consistently before and after birth.…”
Section: 4mentioning
confidence: 99%
“…Many studies have suggested that epigenetic modification is involved in the abnormal development of multiple organs in offspring exposed to adverse environments during pregnancy. [61][62][63] For example, prenatal dexamethasone exposure could inhibit the H3K27ac level and expression of adrenal IGF1 via the GRα/miR-370-3p/Sirt3 pathway, and programmed the adrenal hypofunction of offspring. 64 In this study, we found that the level of H3K14ac in the promoter region of SR-B1 of the PCE female offspring increased consistently before and after birth.…”
Section: 4mentioning
confidence: 99%
“…Beyond the proximal risk factors of prenatal use of alcohol and other teratogenic drugs, many other variables contribute to the variation and severity of child outcomes. Certainly, genetic and epigenetic traits of both the father and mother (Chung et al, 2021;Thomas et al, 2023) play a role in outcome and trait severity; but multiple other, more distal factors, also contribute to phenotypic variation (McQuire et al, 2020;Montag, 2016;Roozen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the proximal risk factors of prenatal use of alcohol and other teratogenic drugs, many other variables contribute to the variation and severity of child outcomes. Certainly, genetic and epigenetic traits of both the father and mother (Chung et al., 2021; Thomas et al., 2023) play a role in outcome and trait severity; but multiple other, more distal factors, also contribute to phenotypic variation (McQuire et al., 2020; Montag, 2016; Roozen et al., 2018). A pregnant woman's nutritional status has been proven influential, for multiple nutritional deficiencies have been associated with more dysmorphia, cognitive and behavioral delays, and growth restriction (Carter et al., 2017; Huebner et al., 2015; May et al., 2014; Wozniak et al., 2015; Zeisel, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of ‘Fetal Origin of Adult Disease’ (FOAD) and ‘Development Origin of Health and Disease’ (DOHaD) ( 11 , 12 ), an increasing number of studies have linked the endocrine environment during pregnancy to the long-term effects on future generations ( 13 16 ). With lifestyle changes and the effects of exogenous endocrine disruptors ( 17 ), the proportion of women with high androgen levels during pregnancy was significantly increased ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%